Quantum chemistry study on small molecules adsorption and reactivity of Ga/SAPO-11 catalyst - Sierraalta, Anibal; Añez, Rafael; Ehrmann, Elena (Ciencia, 1970)
Quantum chemical calculations were carried out to determine the geometries and the adsorption energies of NH3, SO2, CH3NH2, CH3SH, H2, and H2O molecules on a gallium-exchanged silicoaluminophosphate (SAPO) catalyst. The analysis of the results shows that the formation of the dihydride species [GaH2]+ is thermodynamically unfavorable. Therefore, under H, pressure, the Ga+ as well as [GaH2]+ species are present simultaneously due to the thermodynarnic equilibrium. On the other hand, the reduced Ga species behave like hard acids that react with hard bases such as NH3, and CH3NH2, but do not react with CH3SH which is a soft base. Calculations with small models of 3 tetrahedrons (T3) and with a model of 3 rings of 10 tetrahedrons (3T10) to simulate the SAPO-11 pore, show that in general, the cage effect only influences the magnitude of the reaction energies but not their endothermic or exothermic character.